1899 Utah Laws 42-43, ch. 26, § 24 - (:unkn) unknown (General Publisher, 1898)
It shall be unlawful for any person to use any gun larger than ten-guage while hunting for fowl or birds.
--
Keywords: HUNTING REGULATION